Introduction to digital signal processing using MATLAB - Schilling, Robert J.; Sandra L. Harris ([Singapore] : Cengage Learning Asia Pte Ltd, 2012)
This second edition text focuses on the fundamentals of digital signal processing with an emphasis on practical applications. In order to motivate students, many of the examples illustrate the processing of speech and music. This theme is also a focus of the course software that features facilities for recording and playing sound on a standard PC. The accompanying website contains a comprehensive MATLAB software package called the Fundamentals of Digital Signal Processing (FDSP) toolbox version 2.0. The FDSP toolbox includes chapter GUI modules, an extensive library of DSP functions, direct access to all of the computational examples, figures, and tables, solutions to selected problems, and onliine help documentation. Using the interactive GUI modules, students can explore, compare, and directly experience the effects of signal processing techniques without any need for programming.
Part I: Signal and system analysis -- 1. Signal processing -- 2. Discrete-time systems in the time domain -- 3. Discrete-time systems in the frequency domain -- 4. Fourier transforms and spectral analysis -- Part II: Digital filter design -- 5. Filter design specifications -- 6. FIR filter design -- 7. IIR filter design -- Part III: Advanced signal processing -- 8. Multirate signal processing -- 9. Adaptive signal processing -- Appendix 1. Transform tables -- Appendix 2. Mathematical identities -- Appendix 3. FDSP toolbox functions.
Includes bibliographical references and index.
Keywords: MATLAB